2020
DOI: 10.3390/foods9040431
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Mango Fruit Leathers with Natal Plum (Carissa macrocarpa) Improves Their Phytochemical Content and Antioxidant Properties

Abstract: Natal plum fruit (Carissa macrocarpa) is indigenous to South Africa and a rich source of cyanidin derivatives. Indigenous fruits play a major role in food diversification and sustaining food security in the Southern African region. Agro-processing of indigenous are practiced adopted by the rural African communities in order to reduce the postharvest wastage of fruit commodities. In the current study, Natal plum was added to mango pulp at different ratios (mango and Natal plum (5:1, 3:1, 2:1)) to develop a heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
(72 reference statements)
0
6
0
1
Order By: Relevance
“…It was introduced into the United States in 1886 by the horticulturist [3]. Carissa macrocarpa commonly known as Natal plum, native to the coastal region of Natal, South Africa and consumed as edible fruits [4]. The plant also cultivated in Egypt El-Orman garden and grows as a shrub (3-4 m height).…”
Section: Introductionmentioning
confidence: 99%
“…It was introduced into the United States in 1886 by the horticulturist [3]. Carissa macrocarpa commonly known as Natal plum, native to the coastal region of Natal, South Africa and consumed as edible fruits [4]. The plant also cultivated in Egypt El-Orman garden and grows as a shrub (3-4 m height).…”
Section: Introductionmentioning
confidence: 99%
“…54 A recent study reported that incorporation of C. macrocarpa fruit into mango fruit pulp affords functional food possessing betterquality dietary phytochemical content and nutritional value. 56 In consideration of the utilisation of C. macrocarpa as an agricultural resource, crude phenolic and terpenoid extracts of the leaves, administered at a concentration of 10 mg/mL, demonstrated significant in vitro inhibition of Aphis fabae (a devastating bean pest). Accordingly, the leaf extracts can act as a natural pesticide alternative to petroleumbased synthetic pesticides.…”
Section: Natal Plum (Carissa Macrocarpa)mentioning
confidence: 99%
“…The fresh pulp, as a tradition, is processed into juice, jam, marmalade, puddings, and porridge, or sundried for storage. 56 Diverse parts of V. infausta are used in the traditional treatment of various kinds of diseases and health disorders, as summarised in Table 1.…”
Section: Wild Medlar (Vangueria Infausta)mentioning
confidence: 99%
“…Produk ini tinggi serat dan karbohidrat, namun rendah lemak. Teksturnya kenyal, rasanya enak, dan dapat dikonsumsi sebagai camilan manis (Mphaphuli et al, 2020). Fruit leather memiliki kelebihan, yaitu masa simpannya cukup lama, mudah untuk dibuat, dan nilai gizi yang terkandung didalam produk ini tidak banyak berubah (Tondang et al,…”
Section: Kajian Pustakaunclassified